Comparison of Plasma Neurosteroid and Prolactin Levels in Patients with Schizophrenia and Healthy Individuals - Forough Riahi; Maryam Izadi-mazidi; Ali Ghaffari; Elham Yousefi; Shahram Khademvatan (Scientifica)
Background. The present study aimed to compare plasma levels of cortisol, testosterone, dehydroepiandrosterone (DHEA), and prolactin in patients with schizophrenia and healthy individuals. Method. A total of 100 patients with schizophrenia disorder (69 men and 31 women) and 190 healthy individuals (94 men and 96 women) participated in this cross-sectional study. They were tested for hormone levels and completed demographic questionnaires. Data were analyzed using multivariate analysis of variance (MANOVA) and one-way analysis of variance. Results. Serum testosterone level was significantly higher in men with schizophrenia than in healthy men. Women with schizophrenia had a significantly higher level of testosterone and lower level of prolactin compared to healthy women. There were no significant differences in hormone levels across various subtypes of schizophrenia. No significant differences also were observed in hormones levels in patients with first-episode schizophrenia disorder compared to those in patients with recurrent episodes. Conclusion. This study indicated that abnormal testosterone and prolactin levels might be associated with pathophysiology of schizophrenia disorder.